2016
DOI: 10.1038/ncomms11208
|View full text |Cite|
|
Sign up to set email alerts
|

Large-scale production of megakaryocytes from human pluripotent stem cells by chemically defined forward programming

Abstract: The production of megakaryocytes (MKs)—the precursors of blood platelets—from human pluripotent stem cells (hPSCs) offers exciting clinical opportunities for transfusion medicine. Here we describe an original approach for the large-scale generation of MKs in chemically defined conditions using a forward programming strategy relying on the concurrent exogenous expression of three transcription factors: GATA1, FLI1 and TAL1. The forward programmed MKs proliferate and differentiate in culture for several months w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
249
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(271 citation statements)
references
References 67 publications
8
249
2
12
Order By: Relevance
“…More recently, the combinatorial expression of TAL1 with GATA2 was found to induce a haemogenic endothelial phenotype biased towards erythro-MK differentiation from hPSCs [237]. Proceeding from a methodically curated list of candidate genes, we found that the minimal combination of GATA1, FLI1 and TAL1 results in the highly efficient production of MKs from an array of hPSC lines in chemically-defined serum-free conditions and with minimum cytokine input [238]. None of these three TFs by itself or a combination of two could efficiently induce forward programming and impose MK identity to hPSCs.…”
Section: Mks and Platelets From Human Pluripotent Stem Cellsmentioning
confidence: 90%
“…More recently, the combinatorial expression of TAL1 with GATA2 was found to induce a haemogenic endothelial phenotype biased towards erythro-MK differentiation from hPSCs [237]. Proceeding from a methodically curated list of candidate genes, we found that the minimal combination of GATA1, FLI1 and TAL1 results in the highly efficient production of MKs from an array of hPSC lines in chemically-defined serum-free conditions and with minimum cytokine input [238]. None of these three TFs by itself or a combination of two could efficiently induce forward programming and impose MK identity to hPSCs.…”
Section: Mks and Platelets From Human Pluripotent Stem Cellsmentioning
confidence: 90%
“…Moreau et al [65] described the generation of high yields of MKs by chemical forward programming (fop) of hPSCs based on the overexpression of GATA1, FLI1 and TAL1. FopMKs tolerated cryopreservation, and PLTs appeared to be functional as revealed by spreading on fibrinogen as well as in vivo thrombi formation.…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…Alternatively, and although initial studies have used ibroblasts [61][62][63], UCB may be reprogrammed to induced pluripotent stem (iPS) cells [64], which can then be diferentiated into diferent cell lineages, e.g., to generate red blood cells and platelets. As these end cells lack nuclei, they may allay certain safety concerns with respect to iPS cells and tumorigenicity (provided that enucleated cells can survive transplantation).…”
Section: Other Uses Of Ucbmentioning
confidence: 99%